UNDER WATER LAMP COLOUR LAMP EFFECT TO CATCH OF FISH WITH USE KELONG (LIFT NET) IN MALANG RAPAT VILLAGE DISTRICT GUNUNG KIJANG BINTAN REGENCY PROVINCE KEPULAUAN RIAU - Rakesh Sukrillah; Arthur Brown; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in September 2015 in the village of Malang Meeting Gunung Kijang Bintan regency of Riau Islands Province. The purpose of this study was to determine whies colour of the light is bring the best catches of kelong. This experimental are composible elboot blue and yellow submesible lamps on kelong catches. Results of this study showed that blue submesible lamp nigher catches no much 140,5 Kg while yellow submesible lamp only 90 Kg.Keywords:Under Water Lamp (LACUBA), Light, Kelong (Lift Net)